Open foot stance reduces lead knee joint loading during golf swing - Stokes, H.; Escamilla, R.; Bellapianta, J.; Wang, H.; Beach, T.; Frost, D.; Zheng, N. (Journal of Applied Biomechanics, 2023)
Foot stance and club type`s relationship with lead knee joint biomechanics and possible involvement with injury incidences in amateur golfers have not been evaluated. This study included 16 male right-handed amateur golfers who performed golf swings with 2 different foot stances (straight and open) using 4 different club types (driver, 3 iron, 6 iron, and 9 iron) while standing on 2 force plates in a motion capture laboratory. A custom program calculated the kinematics and kinetics of the lead knee. Overall, the open stance reduced most translations, rotations, forces, and torques of the lead knee in all 4 club types when compared with the straight stance. The open stance reduced the rotation motion (-28%), compressive force (-5%), and rotation torque (-9%) when compared with the straight stance, which are the highest contributors to grinding of cartilage. The driver club had significantly larger values in most translations, rotations, forces, and torques when compared among the 4 club types. The open stance reduced the rotation motion, compressive force, and rotation torque in the lead knee joint compared with the straight stance. Lead knee joint biomechanics should be monitored to reduce injury in amateur golfers.